Paraphrasing a peer's utterances to develop the students' speaking fluency - Suseno, Edy (Journal of Education Method and Learning Strategy, 2023)
The majority of EFL students get stuck in conversation practice. Ten freshmen joined the treatment to correct such a flaw. They equip themselves with equipment connected with stable internet access. The teacher created a whatsapp group to begin the course. He updated the application with the pupils' contacts. The students formed pairs to make the teaching and learning process easier. The teacher gave each duo a URL to click on, listen to, and learn from. They talked about the material's content. After it is over, each group designates a representative to give the discussion's outcome in front of the class. He must also paraphrase his partner's viewpoint. After the presentation, there was a question-and-answer period. The teacher gave the evaluation once all participants had finished performing. The information gathered during the procedure was qualitatively examined. The students' speaking skills improved as a result. The teacher might modify these findings to teach the associated disciplines. It also inspires other researchers to conduct more research.